QTL mapping for resistance of maize to grey leaf spot. Issue 3 (19th December 2017) - He, Wenzhu; Yang, Lin; Leng, Yifeng; Zhang, Biao; Yang, Junpin; Li, Lujiang; Chen, Yunping; Kang, Jiwei; Tang, Haitao; Deng, Luchang; Wu, Yuanqi; Cao, Moju; et al.
Abstract: Grey leaf spot (GLS) is a global maize leaf disease that seriously endangers maize production. Discovering and utilizing genetic loci for GLS resistance would be useful for breeding new varieties with improved resistance. In this study, 233 F2:3 families (produced from the susceptible inbred line 08‐641 × the resistant inbred line 446) were used for quantitative trait locus (QTL) mapping of resistance to GLS. Five GLS resistance QTLs were detected on chromosomes 1, 2, 3, 4, and 6, which explained 6.7%‐21.3% of the phenotypic variation. The QTLs, qRgls . CH‐4, qRgls . CH‐1, qRgls . CH‐2, and qRgls . CH‐6, were stably expressed in the four environments, and all loci for GLS resistance were derived from the resistant parent, 446. The additive effects of qRgls . CH‐4, qRgls . CH‐1, and qRgls . CH‐6 were significantly greater than their single dominant effects, which may be beneficial for GLS resistance breeding. The QTL qRgls . CH‐6, located in bins 6.02–6.05, did not overlap with any previously reported resistance QTL and thus was identified here for the first time. QTL analysis of PI (leaf performance index) detected three leaf function QTLs on chromosomes 4, 8, and 9 were related to GLS resistance and explained 4.8%‐6.2% of the phenotypic variation. Among them, qPI . CH‐4 was significantly stronger expressed in several environments; this allele associated with increased leaf function came from the resistant parent, 446, and its interval overlapped with that of qRgls . CH‐4 . Furthermore, both qRgls . CH‐4 and qPI . CH‐4 were located in a hotspot area for GLS resistance in bins 4.05‐4.06, indicating that GLS resistance was significantly related to leaf performance and that GLS significantly reduced leaf photosynthetic performance.